Addition of Aripiprazole to the Clozapine May Be Useful in Reducing Anxiety in Treatment-Resistant Schizophrenia - Chanachev, Aleksandar; Ansermot, Nicolas; Crettol Wavre, Séverine; Nowotka, Ute; Stamatopoulou, Maria-Eleni; Conus, Philippe; Eap, Chin B. (Case Reports in Psychiatry, 2011)
There exist many case reports and studies on the antipsychotic augmentation by aripirazole in partial responders to clozapine, the most seem to be finding a slight difference in the PANSS and CGI scores after the aripirazole addition. The results of our report are compatible with those of other studies but, we have found a considerable antianxiety action in both of the cases. The 5HT1A agonism of aripirazole could be hypothesized as mechanism contributing to this effect.